EBNA1 can link the enhancer element to the initiator element of the Epstein-Barr virus plasmid origin of DNA replication. - Middleton, T (1992)
The plasmid origin of DNA replication of Epstein-Barr virus, oriP, is replicated once per cell division, employing cellular replication machinery and only one viral protein. To understand how replication from this origin is initiated and regulated, we purified this viral protein, EBNA1. EBNA1 was expressed in CV-1p cells by using an infectious simian virus 40 vector containing the EBNA1 gene. It was purified in two chromatographic steps to apparent homogeneity. The purified protein is capable of supporting transcription of the luciferase gene from a reporter plasmid carrying the FR enhancer element to which EBNA1 binds. EBNA1 does not have oriP-dependent ATPase activity, indicating that it does not carry out an energy-dependent step in the initiation of DNA replication. However, EBNA1 does mediate an association between the two elements of oriP. We measured this association by binding one of the elements, the enhancer element, to a solid matrix and measuring retention by this element of the other one, the initiator element, in the presence of EBNA1. This retention is specific for DNA fragments containing EBNA1-binding sites. EBNA1 thus can link the two elements of the origin, providing a locally high concentration of EBNA1 at the site of initiation of DNA replication. We propose that this association is important either (i) to affect DNA structure to allow a cellular helicase to initiate DNA strand separation or (ii) to bind replication proteins to bring them to the origin of replication.